Water depths for different soybean cultivars in center pivot - Gava, Ricardo; Lima, Sebastiao F. de; Santos, Osvaldir F. dos [UNESP]; Anselmo, Jefferson L.; Cotrim, Mayara F.; Kuhn, Irineu E. (Univ Federal Campina Grande, 2018)
Reductions in soybean yields are mainly linked to the occurrence of dry spells, which are becoming more frequent due to climate change. Thus, the aim of this study was to evaluate soybean cultivars irrigated with different water depths under center pivot. The experiment was conducted during the 2014/15 growing season, under center-pivot irrigation in Chapadao do Sul, MS, Brazil. The design was a randomized block in split plot with four replicates, where plots consisted of 4 water depths (0, 50, 75 and 100% of crop evapotranspiration - ETc) and the subplots of 6 soybean cultivars (NA 5909 RR, DM 5958 IPRO, Anta 82 RR, M 7110 IPRO, Desafio RR, M 7739 IPRO). The cultivar Desafio RR was the one that best responded to irrigation, increasing yield to 6174 kg ha(-1) against 3798 kg ha(-1) under rainfed condition. The highest yield under rainfed condition was obtained by the cultivar NA 5909 RR, reaching 4806 kg ha(-1). This shows that some cultivars can respond positively to irrigation, resulting in increased yield, depending on the genetic characteristics of each one.
Keywords: Glycine max (L.) Merrill; drought; water deficit